Stochastic integral of Hitsuda–Skorokhod type on the extended Fock space - Kachanovskii, N. A.; Tesko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We review some recent results related to stochastic integrals of the Hitsuda–Skorokhod type acting on the extended Fock space and its riggings.